Kompetensi Pustakawan IAIN Kudus dan UIN Walisongo Semarang dalam penulisan karya ilmiah - Wiji Suwarno (Jurnal Informatio, 2021)
This research takes the theme of the problems of librarians in producing written works. The purpose of this research is to describe the competence of librarians in writing in the present era, and to reveal the problems faced by librarians in producing written works, seen from the supporting factors as well as from the librarian barrier factors in writing.  Qualitative research is kind of the research used in this research, with a phenomenological approach. Interviews, observation and documentation as a data collection method. This study took informants from librarian elements who were then referred to as research subjects from IAIN Kudus and UIN Walisongo Semarang as research locus. The results of this study are that the writing competence of PTKIN librarians has penetrated the world of publications both in print and virtual, both the carrying capacity of writing competencies depends on cultural and structural support capacity and librarian obstacles in writing are plagiarism concerns, lack of reading activity, difficulty determining topics, laziness, lack of mastered references, and low credit numbers.